Experimental study on the contribution of masonry infill in the behavior of RC frame under seismic loading. (15th June 2018) - Dautaj, Arton D.; Kadiri, Qani; Kabashi, Naser
Highlights: Eight 2/3 scale, single-bay, single-story RC frame specimens were tested. Analysis results show that masonry unit type influenced RC frame failure mode. The strong frame–weak infill was proposed for the seismic design of infilled frames. Abstract: An experimental investigation is conducted to study the behaviour of masonry-infilled reinforced concrete (RC) frames with various lateral strengths. In addition, we study the behaviour of masonry units when the masonry walls are erected after the RC frame is cast. This construction technique is widespread in Kosovo. Eight 2/3 scale, single-bay, single-story RC frame specimens were tested. Six were infilled with hollow clay block masonry units and combined with RC frames with various strengths, one was infilled with solid clay bricks, and one was without infill (bare frame). The test results showed that the type of masonry unit influenced the failure mechanism of the masonry-infilled RC frames. Further, the results show that the main failure modes of the masonry-infilled RC frames, infilled with hollow clay blocks was the shear failure of the masonry infill, beam column joint failure, and the formation of flexural hinges in the part of RC frame. Whereas, the main failure mode of the masonry-infilled RC frames infilled with solid clay bricks was shear failure of the column and the masonry infill. Based on the experimental results, minimum lateral design strength criteria for RC frames infilled with hollow clay blocks is proposed in order to ensure the controlled ultimate failure mechanism.